Discussion on “Design of acid-geopolymers based on clays by-products for methylene blue removal from wastewater” [Applied Clay Science 245 (2023) 107126] - Bollinger, Jean-Claude; Chu, Khim Hoong; Mouni, Lotfi; Salvestrini, Stefano (Applied clay science, 2024)
The subject paper deals with the sorption of dyes (mainly methylene blue) on originally prepared geopolymers based on clay-rich wastes from the phosphate industry. However, the results of sorption experiments are marred by errors of interpretation that limit their validity. In particular, it is well known that linearization of the equations used to model sorption kinetics (pseudo-first and pseudo-second order) and isotherms (Langmuir and Freundlich) should be avoided, as this may bias the calculated values. In addition, other selected models use incorrect equations, as in the case of the intra-particular diffusion kinetic model and the Temkin isotherm. Some additional results are inaccurate or illogical, such as the study of the influence of pH. We hope that our comments and suggestions will serve to correct the discussed paper and avoid repetition of these errors in future scientific literature.